2019
DOI: 10.1080/23299460.2019.1653154
|View full text |Cite
|
Sign up to set email alerts
|

Creating relevant knowledge in transdisciplinary research projects - Coping with inherent tensions

Abstract: Transdisciplinarity aims to address 'grand societal challenges' especially in the sustainability area through realizing 'alternative' ways of knowledge production which integrate societal actors into research. Yet, despite considerable political and scholarly effort and support, the numerous initiatives and programs devoted to produce 'societally relevant knowledge' often yield rather conventional scientific output. For understanding why this is the case, this research investigates how researchers who were eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
(71 reference statements)
2
16
0
2
Order By: Relevance
“…This aligns with previous research which has found academics and scientists tend to use values such as a commitment to quality, rigour, autonomy and freedom to inform their views on the expected roles and responsibilities of their profession (Degn 2018;Henkel 2005). However, research has highlighted that scientists' also believe that an important part of their role is to demonstrate expertise, and that this is best exemplified by demonstrating excellence in one's specific discipline (Schikowitz 2020), and in the current study, this is where conflicts appeared to arise. Participants discussed how the perceived roles and responsibilities of the scientist are largely shaped by their beliefs around what types of knowledge should drive the research and innovation process, with scientists often favouring scientific knowledge over lay knowledge.…”
Section: Perceived Roles and Responsibilities Of Scientistssupporting
confidence: 81%
“…This aligns with previous research which has found academics and scientists tend to use values such as a commitment to quality, rigour, autonomy and freedom to inform their views on the expected roles and responsibilities of their profession (Degn 2018;Henkel 2005). However, research has highlighted that scientists' also believe that an important part of their role is to demonstrate expertise, and that this is best exemplified by demonstrating excellence in one's specific discipline (Schikowitz 2020), and in the current study, this is where conflicts appeared to arise. Participants discussed how the perceived roles and responsibilities of the scientist are largely shaped by their beliefs around what types of knowledge should drive the research and innovation process, with scientists often favouring scientific knowledge over lay knowledge.…”
Section: Perceived Roles and Responsibilities Of Scientistssupporting
confidence: 81%
“…Interdisciplinary integration within a research organization can help to address such problems, but it may still lack practical engagements with the local knowledges and lived experiences of land managers, regulators and policymakers, or local communities. Transdisciplinary approaches are, therefore, required that purposefully include ‘non-academic’ or ‘non-scientific’ participants [ 15 , 91 , 100 ]. In this sense, responsible research should ultimately lead to collaborative problem framing not only among researchers from multiple scientific disciplines but a variety of actors, and their diverse forms of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of simulation modelling, such transdisciplinary approaches are particularly important when modelled information is intended to contribute meaningfully to the development of policy pathways ([ 98 ]; cf. [ 91 ]). Our experiences regarding agricultural digitalization and associated modelling uncertainties support this view.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations